2012
DOI: 10.1159/000335099
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Susceptibility to Dental Caries on Pit and Fissure and Smooth Surfaces

Abstract: Carious lesions are distributed nonuniformly across tooth surfaces of the complete dentition, suggesting that the effects of risk factors may be surface-specific. Whether genes differentially affect caries risk across tooth surfaces is unknown. We investigated the role of genetics on two classes of tooth surfaces, pit and fissure surfaces (PFS) and smooth surfaces (SMS), in more than 2,600 subjects from 740 families. Participants were examined for surface-level evidence of dental caries, and caries scores for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
48
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 48 publications
7
48
1
1
Order By: Relevance
“…This finding contradicts existing evidence that PF have a greater risk of caries among young children [Batchelor and Sheiham, 2004;Warren et al, 2006;Shaffer et al, 2012;Broffitt et al, 2013]. For example, in the study of Warren et al [2006], while over 30% of PF initial caries progressed to frank decay or filled surfaces in the average 4-year period, very few SM with initial caries did so.…”
Section: Discussioncontrasting
confidence: 61%
“…This finding contradicts existing evidence that PF have a greater risk of caries among young children [Batchelor and Sheiham, 2004;Warren et al, 2006;Shaffer et al, 2012;Broffitt et al, 2013]. For example, in the study of Warren et al [2006], while over 30% of PF initial caries progressed to frank decay or filled surfaces in the average 4-year period, very few SM with initial caries did so.…”
Section: Discussioncontrasting
confidence: 61%
“…Despite the acknowledged importance of genetic factors (Townsend et al, 1998) and estimates of heritability of 30% to 50% (Bretz et al, 2005;Wang et al, 2010;Shaffer et al, 2012b), only a few caries susceptibility genes have been identified and validated thus far.…”
mentioning
confidence: 99%
“…Although caries is a person-level disease, it should be expected that FV may confer different levels of caries protection in surfaces with different caries risk and fluoride retention potential. In fact, a recent study indicated that genetically conferred caries risk may differ between pits and fissures and smooth surfaces in the primary dentition [Shaffer et al, 2012]. Therefore, the specific aim was to determine if the caries-preventive effect of a community intervention that included FV application varied according to tooth anatomy and baseline tooth pathology.…”
mentioning
confidence: 99%